Stylistics between Theory and Practice (Al-Qamar, 2022)
The stylistics is considered one of the main pillars in light of the ancient rhetorical research, despite the control of this research for a period of time on literary critical thought, the emergence of modern linguistics had the merit of sponsoring and caring for this method, providing it with the causes of vitality and resurgence, which led to the decline of the star of this rhetoric and reducing its size, thus opening the way to a new science that competes with the old rhetoric, namely stylistics to keep pace with the current stage, and the science of stylistics, like the various modern monetary currents, has witnessed many transformations since the beginnings of its first appearance, which led to its contact with some critical concepts and their inclusion in them sometimes, and we can represent the path of this method in the form of the sun that alternates and consecutively follows the clouds in the sky, and sometimes it lights up and blocks others.
Keywords: Style; Method; Linguistics; Stylistics